Pre-cueing Effects on Perception, Attention, and Cognitive Penetrability - Athanassios Raftopoulos (Frontiers Research Topics, 2018)
Attention has often been likened to spotlights and filters-devices that illuminate or screen out some inputs in favor of others. This largely passive conception of attention has been gradually replaced by a more dynamic and far-reaching process. We know that attentional processes augment neural processing at all levels, and in some cases, augmenting processing within the sense organs themselves. For example, cueing object features (e.g., instructing a subject to look at a screen for a red object) modulates prestimulus activity in the visual cortex. Far from being limited to space or basic features, such attention cueing can function in surprisingly flexible and complex ways: people can be cued to attend to various objects, properties, and semantic categories and such attention appears to directly involve perceptual mechanisms. Studies of spatial attention cues presented before stimulus presentation show early modulation of perceptual processing. This phenomenon refers to the enhancement of the baseline activity of neurons at all levels in the visual cortex that are tuned to the cued location, which is called attentional modulation of spontaneous activity. The spontaneous firing rates of neurons are increased when attention is shifted toward the location of an upcoming stimulus before its presentation. Evidence also suggests that through pre-cueing of object features, feature-based attention modulates prestimulus activity in the visual cortex. The effects of pre-stimulus feature attention act either as a preparatory activity to enhance the stimulus-evoked potentials within feature sensitive areas, or they act so as to modulate stimulus-locked transients. Both effects of pre-cueing reflect a change in background neural activity. They are called anticipatory effects established prior to the presentation of the stimulus. Thus, they do not modulate processing during stimulus viewing but bias the process before it starts via the increase in the base line firing rates; they rig-up perceptual processing without affecting it on-line. Moreover, recent work on perceptual processing emphasizes the role of brain as a predictive tool. To perceive is to use what you know to explain away the sensory signal across multiple spatial and temporal scales. Perception aims to enable perceivers to interact with their environment successfully. Success relies on inferring or predicting correctly (or nearly so) the nature of the source of the incoming signal from the signal itself, an inference that may well be Bayesian. Current research sheds light on the role of attention in inferring the identities of the distal objects. Attention within late vision contributes to testing hypotheses concerning the putative distal causes of the sensory data encoded in the lower neuronal assemblies in the visual processing hierarchy. This testing assumes the form of matching predictions, made on the basis of an hypothesis, about the sensory information that the lower levels should encode assuming that the hypothesis is correct, with the current, actual sensory information encoded at the lower levels. To this aim, attention enhances the activity of neurons in the cortical regions that encode the stimuli that most likely contain information relevant to the testing of the hypothesis. In this Research Topic we aim to answer two related questions: First, what are the differences between this sort of pre-cueing effects and top-down cognitive influences on perception, and, in general, how do such attentional cuing effects relate to the broader literature on top-down influences on perception? Second, given that attention appears to change perceptual processing and that a form of attention, namely, cognitively-driven (or endogenous, or sustained) attention is a cognitive process, does attentional modulation through pre-cueing constitute cognitive penetrability of perception? Addressing these two questions will shed light on the theoretical underpinnings of cognitive penetrability and the nature of perceptual processing.